Spatio-Temporal Zoning of the Urban Lands’ Functioning for Ensuring the Sustainable Development of the City - ROGATNEV, Yuri Mikhailovich; SCHERBA, Valentina Nikolaevna; NAZAROVA, Olga Sergeevna; FILIPPOVA, Tatyana Anatolevna; DOLMATOVA, Olga Nikolaevna (Journal of Environmental Management and Tourism, 2019)
The problems of the modern land use development in the cities located in the oil and gas producing Siberian regions of Russia are reviewed in the article. The modern scientific ideas about the role of the modern land and property assets in small and medium-sized cities in adverse climatic living environment are explored for this purpose. The study is aimed at improving the method for assessing the current organization of the land use in the municipal city of Nefteyugansk. The methodological provisions of land zoning with due consideration for its socioeconomic value and temporal changes are developed. The methodological provisions for a comprehensive assessment of the land use conditions aimed at using the spatio-temporal land zoning model are improved. The results of the study can be used in the practice of local authorities and legal entities in urban planning, land and property relations, housing and utility services in territorial planning, development of land and property relations in the market conditions, improvement of the land payment system, determination of the land investment attractiveness, and creation of a unified basis for an objective land plot evaluation. The introduction of the results of the study into practice will allow to increase the efficiency of the land use, increase its value, and bring the socioeconomic indicators of the land and property assets of the city to a higher level.